Optimal Taxation in the Forestry Sector in the Congo Basin : The Case of Gabon - Melhado Orellana, Oscar (Washington, D.C. : International Monetary Fund, 2007)
This paper reviews forestry reform in the Congo basin, focusing on Gabon. It argues that the key challenge for the Congo basin countries is to manage their forests in a sustainable manner. It presents the current situation of forestry taxation and forestry reform in Gabon. The paper analyzes optimal taxation in the forestry sector using a static model. The model works from the proposition that tax policy should be used exclusively for revenue purposes and resource preservation should be achieved mainly through legislation and enforcement. It argues that when prices are uncertain the best practice is to tax only profits.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet